Corpus callosum necrosis with psychiatric symptoms resulting from chronic toluene intoxication/exposure: a case presentation - Gülsün, Murat; Uzun, Özcan; Doruk, Ali (Journal of Dependence, 2006)
Abuse of toluene, which is a neurotoxic substance, causes neurological and psychiatric complications. Similar complications may also be seen in people who are exposed to toluene long term in some industries. Decrease of brain volume and generalised substance changes in brain have been found in imaging studies. Progressive neurological and psychiatric changes have been shown to be due to these changes. In this article, a subject was presented who was exposed to toluene at the workshop for 8 years and has suffered corpus callosum necrosis with progressive psychiatric symptoms.
Keywords: Toluene intoxication, exposure; corpus callosum; psychiatric symptoms